Evaluation of the Pozzolanic Activity of Sewage Sludge Ash. (30th August 2012) - Tantawy, M. A.; El-Roudi, A. M.; Abdalla, Elham M.; Abdelzaher, M. A.
Abstract : Raw sewage sludge was characterized by XRD, FTIR, SEM, and TGA techniques and incinerated in temperature range 650–950°C for 2 h. The effect of incineration temperature on the microstructure and pozzolanic activity of the resultant ash was investigated by techniques mentioned above as well as Chapelle test. It was concluded that incineration of sewage sludge affects the microstructure and pozzolanic activity of the resultant ash. During incineration at temperatures lower than 800°C, amorphous silica captures fixed carbon resulting from incomplete combustion conditions whereas at higher temperatures crystallization of amorphous silica was enhanced. Hydration products formed from hydrothermal treatment of silica fume with lime is amorphous whereas that of sewage sludge ash is fibrous. Hence, incineration of sewage sludge ash must be optimized at 800°C to preserve the pozzolanic activity of the resultant ash.